Planning mobile technology adoption initiatives - Machado, Cássio Bobsin; Freitas, Henrique (Revista Gestão da Produção Operações e Sistemas, 2009)
Mobile digital technology is one of the most important recent technological forces. There are around 2.7 billion mobile subscribers worldwide, and this number keeps growing. In Brazil, like almost every other country, mo- bile phones have the fastest adoption curve among new technologies, being used by more than 60% of all Bra- zilians, a percentage far higher than Internet use in the country. This article proposes a theoretical model for planning mobile technology adoption by organizations to interact with their stake-holders. It considers the ex- ternal context, organizational context, foreseen impacts on the organization, on the individual and interaction among them, and the definitions the organization must make. The proposed model is being used in actual field research, in order to get deeper into attributes and identify applicability to real cases. The main objective of the model is to become practical enough to be used by managers who choose to adopt mobile technologies in their companies. Keywords: Mobile, mobile technology, technology adoption.